The HeyL-Aromatase Axis Promotes Cancer Stem Cell Properties by Endogenous Estrogen-Induced Autophagy in Castration-Resistant Prostate Cancer - Lin, Qimei; Cao, Jiasong; Du, Xiaoling; Yang, Kuo; Shen, Yongmei; Wang, Weishu; Klocker, Helmut; Shi, Jiandang; Zhang, Ju (Frontiers in Oncology, 2022)
Treatment of patients with castration-resistant prostate cancer (CRPC) remains a major clinical challenge. We previously showed that estrogenic effects contribute to CRPC progression and are primarily caused by the increased endogenous estradiol produced via highly expressed aromatase. However, the mechanism of aromatase upregulation and its role in CRPC are poorly described. In this study, we report that HeyL is aberrantly upregulated in CRPC tissues, and its expression is positively correlated with aromatase levels. HeyL overexpression increased endogenous estradiol levels and estrogen receptor-α (ERα) transcriptional activity by upregulating CYP19A1 expression, which encodes aromatase, enhancing prostate cancer stem cell (PCSC) properties in PC3 cells. Mechanistically, HeyL bound to the CYP19A1 promoter and activated its transcription. HeyL overexpression significantly promoted bicalutamide resistance in LNCaP cells, which was reversed by the aromatase inhibitor letrozole. In PC3 cells, the HeyL-aromatase axis promoted the PCSC phenotype by upregulating autophagy-related genes, while the autophagy inhibitor chloroquine (CQ) suppressed the aromatase-induced PCSC phenotype. The activated HeyL-aromatase axis promoted PCSC autophagy via ERα-mediated estrogenic effects. Taken together, our results indicated that the HeyL-aromatase axis could increase endogenous estradiol levels and activate ERα to suppress PCSC apoptosis by promoting autophagy, which enhances the understanding of how endogenous estrogenic effects influence CRPC development.